An HDAC3-PROX1 corepressor module acts on HNF4α to control hepatic triglycerides - Sean M. Armour (Nature Portfolio, 2017)
HDAC3 is a critical mediator of hepatic lipid metabolism and its loss leads to fatty liver. Here, the authors characterize the liver HDAC3 interactome in vivo, provide evidence that HDAC3 interacts with PROX1, and show that HDAC3 and PROX1 control expression of genes regulating lipid homeostasis.